Reducing corrections officer stress by improving prison climate: the importance of support and safety - St. Louis, Stacie (The prison journal, 2023)
Prior research has identified the importance of social climate in psychiatric and correctional facilities. In studies of corrections officer (CO) stress, organizational measures are typically the strongest correlates. This article combines these research areas, examining the relationship between prison climate and corrections officer stress. Analyzing data from a sample of 239 officers in a northeastern state, findings indicate that prison climate, particularly system maintenance, contributes to both officers’ work-related and generalized stress and anxiety. Perceptions of inmates’ personal growth are also associated with decreased generalized stress and anxiety. Officers should feel supported and safe at work to improve the prison climate and reduce officer stress.